EVALUATION OF A NOVEL LIQUID CHROMATOGRAPHY TANDEM MASS SPECTROMETRY BASED METHOD FOR VITAMIN D ANALYSIS IN BLOOD - Naz, Sehrish; Aamir, Muhammad; Haroon, Zujaja Hina; Kirmani, Sobia Irum; Ahmed, Nisar; Ali, Sadiq (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate a novel liquid chromatography tandem mass spectrometry based method for serum 25 hydroxy vitamin D (D2 and D3 metabolites) analysis.Study Design: Cross sectional validation study.Place and Duration of Study: Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Pakistan, from Mar 2019 to Mar 2020.Methodology: Samples were extracted and 25 OH vitamin-D was separated by means of chromatography and finally quantified via mass spectrometer. A quadrupole- tandem mass spectrometer with Electron spray Ionization coupled to high performance liquid chromatography was adopted for detection and quantitation of 25-hydroxyvitamin D2 and D3 in serum.Results: Limit of detection (LOD) was at the level of 2.49 ng/ml and limit of quantitation (LOQ) was estimated to be 3.9 ng/ml for both the metabolites. The correlation coefficient was 0.99. For D3 observed recovery was 98% and 97.5% respectively while for D2 the recovery was calculated to be 97% and 98%. Percentage relative standard deviation (RSD) was 0.8% and 1.3% respectively. This method has an advantage of less matrix effects, minimal cross-reactivity with 24, 25 hydroxy vit D and 25, 26 di-hydroxy vitamin D metabolite than the routinely used antibody-based assays.Conclusion: This LC-MS/MS methodology is sensitive, specific and can quantitate Vitamin D2 and D3 quite efficiently. This method may be employed for vitamin D analysis in clinical laboratories.